2020
DOI: 10.12659/msm.921947
|View full text |Cite
|
Sign up to set email alerts
|

Ferroptosis in Low-Grade Glioma: A New Marker for Diagnosis and Prognosis

Abstract: Departmental sources Background:The extent of glioma resection influences the overall survival (OS) and progression-free survival (PFS). Ferroptosis is a newly recognized type of cell death, which may be associated with low-grade glioma border detection and OS. This study is assessed an optimized ferroptosis gene panel for glioma treatment. Material/Methods:We obtained 45 reports on ferroptosis-related proteins in PubMed and conducted a statistical test of the patients' overall survival (OS) in the TCGA GBMLGG… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
28
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 29 publications
(30 citation statements)
references
References 28 publications
2
28
0
Order By: Relevance
“…It was surprising that ALOX12 and ALOX15 , which are two members of lipoxygenase family, seemed to be unaltered due to very low expression in these groups. In consistent with our result, a previous study also illustrated unalterations of ALOX12 and ALOX15 in different glioma grades 47 . In contrast, it was intriguing that the differential expression of ALOX5 was observed among GBM, LGG, and NON‐TUMOR tissues.…”
Section: Discussionsupporting
confidence: 93%
“…It was surprising that ALOX12 and ALOX15 , which are two members of lipoxygenase family, seemed to be unaltered due to very low expression in these groups. In consistent with our result, a previous study also illustrated unalterations of ALOX12 and ALOX15 in different glioma grades 47 . In contrast, it was intriguing that the differential expression of ALOX5 was observed among GBM, LGG, and NON‐TUMOR tissues.…”
Section: Discussionsupporting
confidence: 93%
“…Mesenchymal stem cells (MSCs) are a type of non-hematopoietic stem cells originated from the stroma, which can alleviate hepatocyte damage and accelerate liver regeneration, participate in anti-inflammatory effects, and regulate immunity [ 16 21 ]. In this study, we aimed to explore the protective effects of bone marrow MSCs (BMMSCs) combined with NMP on DCD donor livers, from a new perspective on ferroptosis of hepatocytes, in order to provide new basic medical evidence for this type of preservation scheme for DCD donor livers.…”
Section: Introductionmentioning
confidence: 99%
“…Genetic inhibition of CISD1 increased iron-mediated intramitochondrial lipid peroxidation, which contributes to erastin-induced ferroptosis [ 28 ]. Previous studies have shown that CISD1 was related to survival of glioma [ 30 ], and high CISD1 expression is a marker of better outcome in glioma [ 31 ]. Glutathione is important for a variety of biological functions, including protection of cells from oxidative damage by free radicals, detoxification of xenobiotics, and membrane transport.…”
Section: Discussionmentioning
confidence: 99%